Urbanismo Paramétrico: Metodologia Digital para um Plano Urbano - Guilherme Manuel Martins Pinto (2013)
This work is focused on the subject of Parametric Urbanism: discussing and questioning about the emergence of this new architectural methodology; addressing the factors that contributed to their appearance; and seeking to understand whether this approach has benefits and whether they may or may not be a solution to urban plans. The work is organized into three parts: the first part provides a brief literature review on the parametric urbanism, which presents historical contextualization and technological Parameterization, its application in architecture, as well as development of Parametric Urbanism. The second part is characterized by a practical case study of parametric urbanism of an Urban Plan in Beijing, developed in an academic context, at the University École Polytechnique Fédérale de Lausanne in 2012 under the supervision of Dr. Jeffrey Huang. From examples of parametric urbanism it is tried to identify and justify decisions defining principles and application guidance for this project. In the conclusion, the third part of the present work, it is presented the final considerations on opposing the case study with the theoretical approach, presented in the beginning, seeking to clarify whether this new form of urban design, Parametric Urbanism, is or not a viable methodology. It is not a intent of this academic research project to endorse a use of Parametric Urbanism as single or exclusive method for developing / obtaining quality urban plans, it is however intent to address a critical view to this new practice of urban design, increasingly present in offices around the world, investigating about their ideals and goals.